Analysis of Wheat Farmers’ Knowledge Level of Advanced Irrigation Systems in The Al-Na’imah Area of Salah Al-Din Governorate - Abdullah, Rasha Raad (American Journal of Botany and Bioengineering, 2026)
This research aimed to identify the level of wheat farmers’ knowledge of advanced irrigation systems in the Al-Na’imah area of Salah al-Din Governorate. It also analyzed the relationship between this knowledge level and several independent variables, namely: age, educational attainment, years of experience in agriculture, cultivated area, type of land ownership, and access to information sources. The research population consisted of all 200 wheat farmers in the area, from which a simple random sample of 12.5% was selected, resulting in a sample size of 25 farmers. The study employed a two-part questionnaire; the first part contained data related to the independent variables. The second part consisted of (23) items to measure knowledge levels using a two-choice scale (yes/no), where (1) was awarded for a (yes) answer and (0) for a (no) answer. The results showed a significant knowledge gap among farmers, with approximately 80% falling within the medium to low knowledge levels. The results also revealed a positive and significant correlation between knowledge level and both academic achievement. The number of years of farming and access to information sources indicate that higher levels of these variables are associated with higher levels of knowledge. Conversely, a significant negative correlation was found between knowledge levels and age, suggesting that advancing age is associated with lower levels of knowledge. Regarding cultivated area and land ownership, no significant correlation was found between them and knowledge levels, reflecting the limited influence of these two variables on farmers’ agricultural knowledge. In light of these findings, the research recommends strengthening extension services and providing modern and diverse information sources to enhance farmers’ knowledge and encourage them to adopt modern irrigation techniques in the region.